Not quite Snow White - Franklin, Ashley (Harper, an imprint of HarperCollinsPublishers, 2019)
Tameika is excited to audition for the school's Snow White musical, but when she overhears her classmates say she is too tall, chubby, and brown to play Snow White, she questions whether she is right for the part.